Strategi Peningkatan Pendapatan Asli Daerah (PAD) Melalui Retribusi Objek Wisata (Studi Kasus di Dinas Pariwisata dan Kebudayaan Kabupaten Bangli) - Andika A, I. B. Restu Surya; Yudartha, I Putu Dharmanu; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2018)
ABSTRACT This research was conducted at the Department of Tourism and Culture of Bangli Regency. This study uses case study using qualitative descriptive research type. The unit of analysis in this study is an organization with informants are leaders, staff and staff who know the detailed information about the strategic planning of the organization and the community of tourism object managers as the subject of policies implemented by the organization. The purpose of this study is as an instrument to determine the extent to which the effectiveness of the strategy and its application as a follow-up and revision to the design of program formulation and the next strategy. Technique of data collecting done by field study that is collecting data through observation, interview and documentation study. The analysis results obtained that the implementation of strategies implemented in the Department of Tourism and Culture of Bangli Regency has several obstacles in the process of organizational strategic planning. Keywords: Local Revenue (PAD), Retribution of Tourism Objects, Tourism Potency, Strategic Plan